Pengaruh Bounding Exercise Programme (Bep) Single Leg Dan High Intensity Interval Training Terhadap Peningkatan Vo2max - Munandar, Rizky Aris; Fauqi, Amal Fauqi; Zen, Mohammad Zaim; Hidayat, Taufiq (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Good physical condition is needed to support achieving maximum performance, so proper training is needed, such as the Single Leg Bounding Exercise Program (Bep) and High Intensity Interval Training. The purpose of this study was to examine and analyze the differences in the effect of these exercises on increasing VO2max. This study used a randomized group pretest and posttest design. The population in this study were male students of the STKIP YAPIS DOMPU Study Program class of 2021, a total of 160 people. The sampling technique used random sampling with a total sample of 36 people, divided into 3 groups, namely the Single Leg, High Intensity Interval Training group and the last, the control group. This type of research is quasi-experimental, with a quantitative approach. Data was collected using measurement techniques using the Fitmate Pro tool to measure VO2max. Data were analyzed using the MANOVA technique, using α 0.05. The results showed that the effect of tabata training on increasing strength with a value of p=0.000, tabata training on increasing speed with a value of p=0.000, then the effect of high intensity interval training on increasing strength with a value of p=0.000, the effect of high intensity interval training on increasing speed with a value of p = 0.000. From the two exercises, it turns out that high intensity interval training is better than tabata training in increasing strength and speed.